The Use of Audio Interpretive Materials in the Development of Tuneful Ear - Grauzdiņa, Ilma (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
The report is devoted to the one of the contemporary ways in the development of tuneful ear related to intensive use of varied audio interpretive materials during musical classes. Sound of “Live music” imparts new sense to such conventional forms of ear training as rhythm dictation, musical dictation, harmonic analysis. It makes possible to train timbral ear, to improve attention, reaction speed, memory as well as noticeably widens musical horizon of pupils. This method has been widely used in France since the end of the 20th century therefore the article looks closely into one of the French encased set. Analysis of French edition proves that this experience should be popularized amidst Latvian music teachers too and analogical edition can be created on the basis of Latvian music.